The planning process around an integrated transport Node/Station: indingilizi - Nyanda, Nduduzo (My University, 2019)
The South African minibus taxi industry is responsible for providing transport for more than 60% of the population and workforce in urban areas, but it is still regarded as informal. This rendering of it as informal can be traced back to the apartheid era and the structural laws put in place by the government, which still are continued in post-apartheid South Africa. In trying to address this at a local level, Cities like Johannesburg have initiated a transit oriented development programme, which aims to incorporate the minibus taxi industry into the bus rapid transit system, and use it and the development of its support infrastructure to drive economic growth and development along key strategic routes/corridors throughout the City (The Corridors of Freedom). As well cutting down on congestion, the programme is meant to redress the socio-political and economic disparities created by apartheid spatial planning, using a bus transit system to ‘re-stitch’ the racially and economically segregated City back together. This also extended to the minibus taxi industry through their incorporation into the system as shareholders (PioTrans), The first two phases (1A & 1B) of the system (Rea Vaya) which link various parts of Soweto to the Johannesburg CBD are functioning, with most affected taxi entities on-board as shareholders of the system. Spatially however, the stations are designed as silos and have not been integrated in with existing transport networks or any surrounding infrastructure. All stations except one, Indingilizi in Dobsonville. Here some attempt has been made to try and house the various transport modes and operators into one transport interchange. From face value, the attempts with Indigilizi seems like a good start at an integrated transport node in the CoF ought to look like, as it tries to integrate the Rea Vaya with the minibus taxis operating in the area. However, upon closer inspection one realises that the systems are in fact not integrated. At best one can say all the operators are just located in (and not even sharing) one space. This speaks to exclusionary nature of the operational design of the node, as even traders have chosen to operate outside along the street and not in the formally built structures in the node. The building’s physical design is also exclusionary as it is fenced off and does not integrate with its surroundings.
School of Architecture & Planning University of Witwatersrand Johannesburg, South Africa, June 2019
Keywords: Transportation--South Africa; Urban transportation--South Africa; Urban transportation--Planning